Do Not Throw Pet Faeces Away: Composted Manures Obtained from Dog and Cat Faeces Contain High Nutrients and Effectively Cultivate Plants - Suwit Wuthisuthimethavee; Jindarha Prempramote; Worakan Boonhoh; Athakorn Promwee; Orachun Hayakijkosol; Tuempong Wongtawan (Recycling)
Dog and cat faeces are a globally neglected issue that demands proper management. The poor handling of pet waste not only impacts environmental health but also contributes to community conflicts due to insufficient waste management practices. The objectives were to investigate the properties of pet wastes compared to livestock wastes (pigs, hens, and cattle) with the intention of formulating an efficient compost product suitable for agricultural applications. Faeces from dogs and cats were collected from the community, while faeces from livestock (pigs, cattle, and hens) were collected from farms. Faeces were mixed with probiotics, rice bran, and rice husk to make compost and used to grow sweet corn plants. The nutrient content was compared between fresh and composted faeces. Composted manure from different animal sources was compared for its effectiveness in promoting sweet corn growth. The results showed that fresh and composted dog and cat manures contained higher levels of nutrients (p < 0.05) compared to livestock manures. Additionally, composted pet manure accelerated (p < 0.05) the growth of the plants compared to composted livestock manures and control groups. This is the first study to conclude that composted pet faeces surpass livestock manure in their higher nutrients and enhance plant growth. The findings could help reduce pet waste and transform it into a valuable recycled resource. However, the safety of composted manure, especially concerning toxoplasmosis from cat faeces, remains a significant concern and requires further investigation.